(untitled) (Archives of Criminology, 2024)
Punishing perpetrators for facilitating illegal border crossings or illegal stays is one of the priorities of the European Union’s migration policy. The author decided to take a look at the practice of such criminal proceedings before Podlasie courts (a region bordering Belarus). In this case, does it truly involve organising an illegal procedure – especially when it comes to family members or co-workers? The purpose of this article, therefore, is to examine the criminal case files of those convicted of organising illegal border crossings – individuals whose behaviour consisted solely of picking up migrants who were already in Poland. Law enforcement authorities charged such people, mainly foreigners, with aiding and abetting the organisation of illegal border crossing. The author addresses the question of whether such behaviour fulfils the elements of the crime specified in Article 264 (3) of the Criminal Code, and what scope of freedom the actors have when deciding on the charges and convictions.